2004
DOI: 10.1093/bja/aeh117
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty in brainstem death testing in the presence of high spinal cord injury

Abstract: In the UK, when the standard brain death criteria are met, further investigations are not necessary. Confirmatory tests can be useful, however, when it is not possible to carry out all of the brainstem tests. We report the case of a patient with multiple trauma and a high spinal cord injury who was apnoeic. Confirmatory tests (EEG, brainstem, auditory evoked potential) were essential in supporting the diagnosis of brainstem death to allow withdrawal of artificial ventilation, as organ donation was being consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Nine Class IV studies have been published on the recognition of brain-death mimics, including fulminant GuillainBarré syndrome, organophosphate intoxication, high cervical spinal cord injury, lidocaine toxicity, baclofen overdose, and delayed vecuronium clearance. [6][7][8][9][10][11][12][13][14] The description of the examinations provided in these studies indicated that a complete brain death examination was not performed in any of these patients. We found no reports in peer-reviewed medical journals of recovery of brain function after a determination of brain death using the AAN practice parameter.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…Nine Class IV studies have been published on the recognition of brain-death mimics, including fulminant GuillainBarré syndrome, organophosphate intoxication, high cervical spinal cord injury, lidocaine toxicity, baclofen overdose, and delayed vecuronium clearance. [6][7][8][9][10][11][12][13][14] The description of the examinations provided in these studies indicated that a complete brain death examination was not performed in any of these patients. We found no reports in peer-reviewed medical journals of recovery of brain function after a determination of brain death using the AAN practice parameter.…”
Section: Analysis Of Evidencementioning
confidence: 99%
“…High cervical cord injury, fulminant Guillain-Barré-syndrome, organophosphate intoxication, baclofen toxicity, lidocaine toxicity, and delayed vecuronium clearance have all been reported as clinical mimics of brain death [7,[11][12][13][14][15][16][17][18]. Neurological findings such as absent brainstem reflexes [15], even including unresponsive pupils [17], may occur temporarily and may present as a false positive sign for the examining physician, particularly if they are not accustomed to performing full neurological and brain death examinations.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…While the three cardinal features of deep unresponsive coma, absent brainstem function, and apnea are widely accepted as key features, the practical aspects of declaring brain death are not standardized. Major differences exist in the requirements of the specialty and training of the assessing physician, the number of observers, timing of the first clinical brain death examination, specifics of the clinical examination, requirement of a repeat examination, duration of observation, and whether and which confirmatory tests are accepted, mandatory, or facilitative [6][7][8][9].…”
mentioning
confidence: 99%
“…53 Second, if cervical spinal cord injury cannot be ruled out or is in fact present, another option may be to do an ancillary test to confirm that brainstem function is irreversibly lost. 54 The absence of blood flow to the brainstem would likely show that the brainstem has died, regardless of cervical spinal cord function. This is problematic for several reasons.…”
Section: Discussionmentioning
confidence: 99%